THE EFFECT OF CELEBRITY ENDORSER TOWARDS PURCHASE DECISION ON BATAM OLEHLO - Sri Zuliarni; Prima Sue Nurlia; Ayu Puspitasari (Politeknik Negeri Batam, 2020)
This study examines the effect of Celebrity Endorser on the purchase decision of Batam Olehlo. Respondents from this study were consumers who have purchased the product of Batam Olehlo. The population in this study is Batam community with a sample of 100 respondents. The sampling technique uses purposive sampling method with the Slovin formula. The data is collected through a questionnaire which is given directly to the respondent. The data analysis method used is descriptive analysis using multiple linear regressions, classical assumption test, t test with a significance level of 0.1, and the coefficient of determination. The results of this study are the three variables of celebrity endorser namely attractiveness, trustworthiness, and expertise partially and simultantly positive and significant effect on the purchase decision.